Pengaruh Human Capital dalam Menjalankan Rencana Strategis Perusahaan - Santi Riana Dewi (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2015)
In this era of global competition, companies need to have a specific competitive advantages over other companies. The ability of an intelligent human capital to able to carry out company’s strategic plan is essential. Corporate excellence can be established through various means such as creating a product with unique design, the use of modern technology, organizational design and the most important is effective human resources management. Products mentioned here are not only in the form of tangible goods and services but olso the intangible ones.